Ciclodextrines interacting with metotrexate via molecular modeling - Vendrame, Laura; Schmitz, Bruna; Fagan, Solange; Zanella, Ivana (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
The coupling of a drug delivery mechanism using nanotechnology is one of the most prevalent approaches in the development of more effective and rapid treatments. This work aimed to evaluate the adsorption capacity of pristine and functionalized cyclodextrins (CD) with the chemotherapeutic drug methotrexate (MTX) in order to decrease toxicity and increase the bioavailability and distribution of the drug mainly in the blood brain barrier. Some studies were carried out through ab initio computational modeling and simulation by the density functional theory (DFT). For all MTX configurations interacting with β-cyclodextrin (βCD), methyl-β-cyclodextrin (Mβ-CD) and hydroxypropyl-β-cyclodextrin (HPβ-CD), the stability of the system was obtained with binding energies ranging from 0.28-0.32 eV, without chemical or structural changes that modify the characteristics of the drug. Through these studies, we can indicate that CDs can interact with MTX and form possible inclusion complexes.